Petrogenesis and detailed geochemical and isotopic studies of the Epembe carbonatite and syenite rocks, NW Namibia - Tshiningayamwe, Mbili (My University, 2022)
Although many carbonatite occurrences world-wide show temporal and spatial association with silica under-saturated alkaline rocks (e.g. nephelinites, ijolites, nepheline syenites) their petrogenetic relationship is still a matter of debate. In the Epembe area of northwestern Namibia, there is an occurrence of a carbonatite associated with alkaline rocks. Such an occurrence provides an ideal opportunity to investigate their petrogenesis and the petrogenetic relationship between them if any. The rocks were studied using whole rock geochemistry, U-Pb geochronology, mineral and isotope geochemistry. The Epembe Alkaline Carbonatite Complex (EACC) was emplaced along a fault zone into medium- to high-grade Palaeoproterozoic basement rocks of the Epupa Metamorphic Complex (EMC) and extends over a distance of 9 km in a south-easterly direction with a width of 1 km. Alkaline rocks constitute the main lithologies and are cross-cut by a calcite-carbonatite dyke. The alkaline rocks can be classified as syenite and nepheline-bearing syenites, with alkalic, metaluminous and ferroan affinities. The syenite occurs as a discontinuous intrusion which separates the nepheline syenite from the EMC, while the carbonatite cross-cuts the nepheline syenite body along strike. The syenite comprises alkali feldspar and clinopyroxene with accessory apatite and magnetite. The nepheline syenite comprises major to minor alkali feldspar, nepheline, biotite and cancrinite, while plagioclase, apatite, sphene, zircon, calcite and magnetite occur as accessory phases. The carbonatite consists of calcite, apatite, pyrochlore, pyroxene (aegirine), biotite, zircon, alkali feldspars and plagioclase in varying amounts. Based on zircon U Pb dating, a 206Pb/238U weighted mean age of 1220 ± 3 Ma (2SE, MSWD = 1.3) was determined for the syenite emplacement, whereas two nepheline syenite samples give identical magmatic ages of 1209 ± 3 (206Pb/238U weighted mean age, 2SE, MSWD = 1.1) and 1205 ± 13 Ma (concordia intercept age, 2SE, MSWD = 2). The nepheline syenite ages correspond with the concordia age of 1198 ± 5 Ma (2SE, MSWD = 1.1) of the carbonatite interpreted as magmatic. The nepheline normative syenites define broadly linear trends in Harker plots consistent with evolution by fractional crystallization involving pyroxene and apatite. The rare earth element (REE) pattern of the syenite shows a negative Eu anomaly, consistent with plagioclase fractionation. The syenite iii is characterized by the absence of a negative Nb anomaly on a Primitive Mantle (PRIMA)- normalized diagram with Ce/Pb and Nb/U ratios of 12 and 19, respectively, suggesting that it was not affected by crustal contamination during ascent and emplacement. The absence of a crustal signature indicates that the syenite is not related to the nepheline syenite by combined assimilation and fractional crystallization, and was likely emplaced as a distinct magma batch derived from the mantle. REE patterns of the nepheline syenite and carbonatite are coherent showing LREE enrichment relative to HREE. On a PRIMA-normalized multi-element diagram both the carbonatite and syenite display relative depletions of Zr, Hf and Pb and relative enrichment of Sr. Low Mg, Cr and Ni contents of the carbonatite and nepheline syenite suggest that these rocks crystallized from an evolved parental magma rather than a primitive mantle-derived melt. Geochemical similarities between the carbonatite and nepheline syenite also suggest that the Epembe carbonatite is not a product of immiscible separation between a carbonate and silicate melt. Instead, the carbonate may represent a melt fraction that formed after partial crystallization of the nepheline syenite. Apatite grains from one syenite, six nepheline syenite and five carbonatite samples were examined using cathodoluminescence (CL) imaging, trace element and Sr-Nd isotope compositions as well as U-Pb geochronology. Syenite-hosted apatite is homogenous in CL and contains the highest concentration of REE (9189-44100 ppm) with light (L) REE enrichment (LaN/YbN = 4-91) relative to heavy (H) REE and negative Eu anomalies (Eu/Eu* = 0.4-0.9). These features are attributed to the formation of apatite in an evolved mantle-derived melt associated with plagioclase fractionation. Nepheline syenite-hosted apatite is also generally homogeneous in CL, while core-rim zoning and patchy textures are only observed occasionally. Both texturally homogeneous and core-rim zoned apatite are enriched in LREE (LaN/YbN = 32-94) relative to HREE, consistent with a magmatic origin. Core-rim zoned apatite is characterized by a rim-ward increase in REE concentrations accompanied by uniform Sr and Nd isotopic compositions, which can be attributed to the re-equilibration of early-formed apatite (core) with later infiltrating melt enriched in REE, causing the formation of apatite overgrowths (rims). Patchy apatite is depleted in Na, Y and REE, particularly the LREE (LaN/YbN = 4-19) and is enriched in Sr relative to apatite from other nepheline syenite, reflecting interaction with fluids (metasomatism). The strontium iv isotope composition of metasomatic apatite and magmatic apatite is indistinct suggesting a magmatic origin of the fluids responsible for alteration. Carbonatite apatite is LREE-enriched (LaN/YbN = 24-161) relative to HREE and displays core-rim zoning in CL accompanied by a rim ward increase in REE, attributed to mineral fractionation. No Eu anomalies (Eu/Eu* = 1) in chondrite-normalized REE patterns are observed in any apatite hosted by nepheline syenite and carbonatite. A LA-ICPMS U-Pb age of 1216 ± 11 Ma (MSWD = 4.3, 2 SE) for syenite apatite constrains emplacement of the syenite, while magmatic nepheline syenite apatite ages of 1193 ± 14 Ma, 1197 ± 17 Ma and 1194 ± 16 Ma (MSWDs < 4.0, 2 SE) have been determined. The Sr and Nd isotopic composition of apatite in syenite (87Sr/86Sr(i) = 0.7035-0.7048; ƐNd(t) = +2.5 to +3.2), nepheline syenites (87Sr/86Sr(i) = 0.7031-0.7037; ƐNd(t) = +1.5 to +4.4) and carbonatite (87Sr/86Sr(i) = 0.7031-0.7033; ƐNd(t) = 0 to +3.3) overlap, pointing to a common but heterogeneous mantle source, possibly involving HIMU and EMI mantle endmembers. Lastly, cathodoluminescence (CL) imaging combined with trace elements (including REE) as well as Hf isotope compositions of zircon grains extracted from one syenite, five nepheline syenite samples and one carbonatite sample are presented. Carbonatite and syenite zircons are generally unaltered and characterized by steeply rising REE patterns in chondrite-normalized diagrams, with positive Ce anomalies (Ce/Ce* = 1-8). Syenite zircon further displays significant negative Eu anomalies (Eu/Eu* = 0.2-0.4) attributed to earlier plagioclase formation and fractionation. These features are consistent with zircon formation in a magmatic environment. In the nepheline syenite samples, two zircon types are recognized. Type 1 zircon is magmatic, with homogeneous-grey, unzoned and oscillatory-zoned domains in CL, while type 2 zircon is hydrothermally altered and displays a cloudy appearance in CL. Type 2 zircon is characterized by enrichment in LREE (101-853 ppm), Nb (97-339) and Ti (63-140 ppm) when compared to magmatic type 1 zircon (LREE = 17-93 ppm, Nb = 7-59 and Ti = 2-15 ppm). The Hf isotope composition of type 1 and type 2 zircon is indistinct suggesting that the fluids involved in zircon alteration were sourced from within the complex. The similarity of ƐHf(t) values in zircon from syenite (+0.5 ± 0.4 to +1.5 ± 0.4), nepheline syenite (+1.6 ± 0.3 to +2.7 ± 0.5) and carbonatite (+0.5 ± 0.4 to +1.9 ± 0.2) is consistent with the melts having been derived from a moderately depleted mantle. v The data presented in this study are best explained by partial melting of a heterogeneous mantle at ca. 1200 Ma, which resulted in the formation of an alkali basalt and a carbonated-alkali basaltic melt. The alkali basalt melt ascended first utilizing an existing fault system and evolved to form the syenite. Subsequently, the carbonated-alkali basaltic melt percolated upwards and differentiated to form the nepheline syenite and calcite-carbonatite. Finally, metasomatic interaction occurred between magmatic derived fluids and primary assemblages.
A thesis submitted in fulfilment of the academic requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Geoscience, University of the Witwatersrand, Johannesburg, 2022